Coastal Development Implications to changes of Coastal Typology in Denpasar City Environment - Atmaja, Dewa Made; Gunamantha, I Made; Bharata, Ida Bagus Arya Yoga (Sriwijaya Journal of Environment, 2025)
The physical development that occurs can change natural landscape units and none other than that is the coastal typology in the coastal area of Denpasar City with high development intensity. This research aims to describe the implications of coastal development on changes in coastal typology in Denpasar City. The method in this research design is quantitative descriptive using QGIS tools for analysis and Landsat satellite image data available on Google Earth Pro for the period December 1990, 2005, and 2020. The results of the research show that in development implications for changes in coastal typology that occur in the coastal area of Denpasar City include the addition or widening of the coastline for the anthropogenic coast coastal typology for the 1990-2005 period which was ±21.12 km long and in the 2005-2020 period it was increased to ±5.14 km long. The widening of the coastline in the marine deposition coast typology experienced an increase of ±1.7 km in the 1990-2005 period. Changes that occurred as a result of development implications that occurred during the 1990-2005 period also included the loss of the marine deposition coast typology along ± 10.61 km. Apart from that, in the same period, ± 1.66 km along the coastal typology of build-by organisms disappeared. Residential settlements on Serangan Island, which included the anthropogenic coast typology, also disappeared during this period for ± 1.18 km.